Analysis of the super high‐speed permanent magnet generator under unbalanced load condition. Issue 8 (26th July 2017) - Qiu, Hongbo; Tang, Bingxia; Yu, Wenfei; Yuan, Shuai; Wu, Jie; Yang, Cunxiang; Cui, Guangzhao
Abstract : In this paper, the 117 kW, 60, 000 r/min super high‐speed permanent magnet generator (SHSPMG) under unbalanced load condition is studied. First, the influence mechanism of the unbalanced load on the generator was revealed, and by using field‐circuit coupling method and at rated load, the current unbalance factor (CUF) was determined. Second, through the time‐stepping finite element method, the generator air‐gap flux was obtained and decomposed in virtue of the principle of Fourier transform. The influence of the unbalanced load on air‐gap flux was studied, and the eddy current loss and torque ripple with different CUFs were calculated and analysed. Finally, based on the calculation results of two‐dimensional transient electromagnetic field, the negative sequence current was extracted by using the symmetrical component method. The research showed that the harmonic content of air‐gap flux density increases when the generator is connected to unbalanced load, and the eddy current loss and the torque ripple increases with the increase of the load unbalance degree. The experimental platform was established and the test data were in good agreement with the model calculated results, which verified the correctness of the model. The research could provide some useful conclusions for the research of the SHSPMG.